2020
DOI: 10.21831/cp.v39i1.29620
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Subjective Well-Being: Does Education Level Take Into Account?

Abstract: Following western trends besides several Asian countries, Indonesian families are experiencing an increase numbers of single men and women which seems to ignore traditional standards ages of getting married for both gentlemen and ladies. Indonesian youth in this category are subjected to social pressure to marry, and this affect their subjective well-being. Using data from Indonesian Family Life Survey (IFLS) 2014; 5th wave with 29,160 participants (15,581 women and 13,579 men) from 15,160 households and 297 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
3
9
0
1
Order By: Relevance
“…Extroverted people were more satisfied with life and happier than their counterparts. This corroborates prior studies that found a positive relationship between extroversion personality traits and subjective well-being in Indonesia (Ndayambaje et al, 2020). Religious people reported being more satisfied with life than their counterparts which is in line with previous studies (Dilmaghani, 2017;Nizeyumukiza et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Extroverted people were more satisfied with life and happier than their counterparts. This corroborates prior studies that found a positive relationship between extroversion personality traits and subjective well-being in Indonesia (Ndayambaje et al, 2020). Religious people reported being more satisfied with life than their counterparts which is in line with previous studies (Dilmaghani, 2017;Nizeyumukiza et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…The literature has shown that gender (Graham & Chattopadhyay, 2013;Nopiyanto, Raibowo, & Prabowo, 2021), marital status (Cao, Krause, Saunders, & Clark, 2015), education (Mrva, 2020) religiosity (Dilmaghani, 2017), personality (Lucas, 2018), social trust (Nizeyumukiza, Cilik Pierewan, Ndayambaje, & Ayriza, 2020), and health (Ndayambaje, Pierewan, Nizeyumukiza, Nkundimana, & Ayriza, 2020) are all related to subjective well-being. Therefore, these variables are susceptible to confound the relationship between physical activity and subjective well-being and will be controlled in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Extroversion personality trait and self-rated health were consistently associated with wellbeing which is in line with prior studies (Lucas, 2018;Ndayambaje, Pierewan, Nizeyumukiza, Nkundimana, & Ayriza, 2020;Ngamaba, Panagioti, & Armitage, 2017;Nizeyumukiza, Pierewan, Ndayambaje, & Ayriza, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The difference in the quality of the learning process of male students and female students based on gender class is very important to note, gender has a direct influence on student learning achievement. Gender factors are also important to note (Josephidou, 2020;Ndayambaje et al, 2020;Nurul Lathifatul Hakimah et al, 2020). Gender does not only mean gender, but also the psychosocial aspects of men and women, so that gender and gender are interrelated terms.…”
Section: Introductionmentioning
confidence: 99%